Trafficking defects in WASH-knockout fibroblasts originate from collapsed endosomal and lysosomal networks - Gomez, Timothy S. (The American Society for Cell Biology, 2012)
The Arp2/3-activator Wiskott–Aldrich syndrome protein and Scar homologue (WASH) is suggested to regulate actin-dependent membrane scission during endosomal sorting, but its cellular roles have not been fully elucidated. To investigate WASH function, we generated tamoxifen-inducible WASH-knockout mouse embryonic fibroblasts (WASHout MEFs). Of interest, although EEA1(+) endosomes were enlarged, collapsed, and devoid of filamentous-actin and Arp2/3 in WASHout MEFs, we did not observe elongated membrane tubules emanating from these disorganized endomembranes. However, collapsed WASHout endosomes harbored segregated subdomains, containing either retromer cargo recognition complex–associated proteins or EEA1. In addition, we observed global collapse of LAMP1(+) lysosomes, with some lysosomal membrane domains associated with endosomes. Both epidermal growth factor receptor (EGFR) and transferrin receptor (TfnR) exhibited changes in steady-state cellular localization. EGFR was directed to the lysosomal compartment and exhibited reduced basal levels in WASHout MEFs. However, although TfnR was accumulated with collapsed endosomes, it recycled normally. Moreover, EGF stimulation led to efficient EGFR degradation within enlarged lysosomal structures. These results are consistent with the idea that discrete receptors differentially traffic via WASH-dependent and WASH-independent mechanisms and demonstrate that WASH-mediated F-actin is requisite for the integrity of both endosomal and lysosomal networks in mammalian cells.